Mindestlohn in Deutschland notwendig: kein Gegensatz zwischen sozialer Gerechtigkeit und Beschäftigung - Gerhard Bosch (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
– Low-wage employment has increased considerably in Germany in recent years due to the erosion of the collective bargaining system. At the same time the structure of the low-wage sector has changed. It has moved to the periphery of the labour market and career development prospects have decreased. Compared with countries that have minimum wages, the downward wage differentiation is very large. This can be corrected by means of a minimum wage without employment losses. Economic theory sees scope for minimum wages by means of productivity increases or when the firms have buyer power (monopsony, oligopsony). The empirical studies on minimum wages show that the employment of adults is not impaired and that there are slight risks in the case of young people. By introducing a minimum wage gradually, as was done in Great Britain, and with parallel evaluation, it is possible to reduce the risks in Germany too. As regards minimum wages it is not only a matter of 'whether or not' but also a matter of 'how'. Minimum wages are a necessary corrective on labour markets with an unequal distribution of power such as those which have developed in Germany.
Keywords: 330; Mindestlohn; Lohnpolitik; soziale Gerechtigkeit; Niedriglohn; Beschäftigungseffekte